High Performance Indium‐Gallium‐Zinc Oxide Thin Film Transistor via Interface Engineering. (1st July 2020) - Zhao, Yepin; Wang, Zhengxu; Xu, Guangwei; Cai, Le; Han, Tae‐Hee; Zhang, Anni; Wu, Quantan; Wang, Rui; Huang, Tianyi; Cheng, Pei; Chang, Sheng‐Yung; Bao, Daqian; et al.
Abstract: Solution‐processed indium‐gallium‐zinc oxide (IGZO) thin film transistors (TFTs) have become well known in recent decades for their promising commercial potential. However, the unsatisfactory performance of small‐sized IGZO TFTs is limiting their applicability. To address this issue, this work introduces an interface engineering method of bi‐functional acid modification to regulate the interfaces between electrodes and the channels of IGZO TFTs. This method increases the interface oxygen vacancy concentration and reduces the surface roughness, resulting in higher mobility and enhanced contact at the interfaces. The TFT devices thus treated display contact resistance reduction from 9.1 to 2.3 kΩmm, as measured by the gated four‐probe method, as well as field‐effect mobility increase from 1.5 to 4.5 cm 2 (V s) −1 . Additionally, a 12 × 12 organic light emitting diode display constructed using the acid modified IGZO TFTs as switching and driving elements demonstrate the applicability of these devices. Abstract : An interface engineering method to regulate the interfaces between electrodes and the channels of indium‐gallium‐zinc oxide (IGZO) thin film transistors (TFTs) is demonstrated by bi‐functional acid modification. This method increases the interface oxygen vacancy concentration and reduces the surface roughness, resulting in three‐fold increased mobility and reduces contact resistance by 75%.